The impact of social media engagement on visibility: a preliminary observation in the Office of Deputy Vice Chancellor Research & Innovation UiTM / Izzat Mohamed Khalil ... [et al.] - Mahat, Mohd Muzamir; Mohamed Khalil, Mohamed Izzat; Azahari, Nur Syazwani; Abd Rahman, Norazah (2023)
This study examines the social media engagement patterns of the Office of Deputy Vice Chancellor Research & Innovation Universiti Teknologi MARA (UiTM). in their efforts to enhance visibility and promote research and innovation among academics. Through strategic content dissemination on Facebook and YouTube, PTNCPI aims to capture attention and inspire active participation within the academic community. By utilizing informational and recognition posters, as well as live and recorded videos, PTNCPI seeks to engage academics by sharing relevant research and innovation content. The analysis of engagement patterns reveals that YouTube's live sessions attract high viewership, while Facebook generates increased engagement through posts related to trending topics and recognition.